2023
DOI: 10.5585/podium.v12i1.20393
|View full text |Cite
|
Sign up to set email alerts
|

Influência do desempenho esportivo e da adesão ao Profut no nível de endividamento de clubes de futebol no Brasil

Abstract: Objetivo do estudo: analisar a influência do desempenho esportivo e da adesão ao Profut no nível de endividamento dos clubes de futebol brasileiros.Metodologia: foram analisados 23 clubes entre o período de 2013 a 2017, por meio de regressão linear com dados em painel, controlando os efeitos fixos.Originalidade/Relevância: há escassez de estudos que analisam a estrutura de capitais dos clubes de futebol, principalmente ao levar em consideração as mudanças contábeis trazidas pela ITG 2003 (2013) e pela Lei 13.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…To incentivize clubs towards transparent, financially balanced management, the Brazilian government passed Law 13,155, as known as the Management Modernization Program and the Fiscal Responsibility of Football (PROFUT) (Santana Filho et al, 2019). PROFUT offers benefits such as deferred payments, reduced interest rates, and penalties on tax and fiscal debts (Ferreira et al, 2023). The program is projected to positively impact Brazilian football clubs' economic, financial, and athletic performance (Umbelino et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…To incentivize clubs towards transparent, financially balanced management, the Brazilian government passed Law 13,155, as known as the Management Modernization Program and the Fiscal Responsibility of Football (PROFUT) (Santana Filho et al, 2019). PROFUT offers benefits such as deferred payments, reduced interest rates, and penalties on tax and fiscal debts (Ferreira et al, 2023). The program is projected to positively impact Brazilian football clubs' economic, financial, and athletic performance (Umbelino et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, existing research on PROFUT's effects on club financial management is not definitive (Ferreira et al, 2023). Some studies claim that PROFUT has improved clubs' financial performance (Marotz et al, 2020;Santana Filho et al, 2019;Silva et al, 2019;Siqueira Junior & Oliveira, 2018), while others have suggested that club indebtedness increased post-PROFUT (Ferreira et al, 2023), implying financial performance deterioration (Umbelino et al, 2019). Hence, this study sought to determine the impact of PROFUT on Brazilian football clubs, financial and athletic performance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations